Analisis Hukum Islam terhadap Praktik Jual Beli Hasil Pertanian Padi Sistem Tebasan di Dusun Kelir Desa Bunder Kecamatan Kabat Kabupaten Banyuwangi - Abdul Kholiq Syafa’at; Rohmatulloh Rohmatulloh (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
The purpose of this study is: To find out the practice of buying and selling agricultural products for the rice slash system in Kelir Village, Bunder Village, Kabat District, Banyuwangi Regency. As well as to find out the review of Islamic Law on the practice of buying and selling agricultural products for rice, the cutting system. This type of research is qualitative research. Data analysis techniques used in this study are interactive models. The result of this research is the practice of buying and selling rice as follows: first the seller will offer rice to the buyer, then the buyer will come to survey and make some estimates regarding the price of rice, after being surveyed will be bargained to reach an agreement with the farmer, after that the slaughterer give a down payment (panjer) as a sign and the balance is paid when the rice is harvested. So from the results of the research that the researchers did, it can be concluded that the provisions of Islamic law on the practice of buying and selling with the slash system in Kelir Hamlet, Bunder Village, Kabat District, Banyuwangi Regency concluded that the practice of buying and selling is legal because it is in accordance with the jizaf sale and fulfillment requirements the condition of buying and selling jizaf itself.